Running Towards Mental Well-Being : Examining the Effects of a Long Distance Running Class on Mental Well-Being - Muehlenkamp, Jennifer J.; Kollman, Samantha; Foltz, Maggie (My University, 2018)
The purpose of this study is to explore the effect of a marathon running class on many of these constructs focusing heavily on grit, body image, and social connect within college students in order to inform decisions regarding possible ways to achieve better mental well-being in college students and therefore improve retention rates and overall success of students.
Color poster with text, graphs, and charts.
Keywords: Posters; Mental health; Running -- Physiological aspects; Running -- Health aspects; Fitness; Mental health -- College students